E-Democracy-- Citizen Rights in the World of the New Computing Paradigms : 6th International Conference, E-Democracy 2015, Athens, Greece, December 10-11, 2015, proceedings /: 6th International Conference, E-Democracy 2015, Athens, Greece, December 10-11, 2015, proceedings. (2015) - Unknown
No abstract available